1991
DOI: 10.1084/jem.174.6.1491
|View full text |Cite
|
Sign up to set email alerts
|

Gorilla class I major histocompatibility complex alleles: comparison to human and chimpanzee class I.

Abstract: 14 gorilla class I major histocompatibility complex (MHC) alleles have been isolated, sequenced, and compared to their counterparts in humans and chimpanzees. Gorilla homologues of HLA-A, -B, and -C were readily identified, and four Gogo-A, four Gogo-B, and five Gogo-C alleles were defined. In addition, an unusual Gogo class I gene with features in common with HLA-A and its related pseudogene, HLA-H, is described. None of the gorilla alleles is identical or even closely related to known class I alleles and eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 36 publications
8
87
3
Order By: Relevance
“…Likewise, an analysis of complete cDNA sequences of 14 HLA-C alleles revealed that HLA-C alleles divide into two groups, one comprising the Cw7 sero-type, and the other group including all remaining alleles. 19 These and other studies have sought to elucidate the sequence relationships of a subset of HLA class I alleles by parsimony or distance-based phylogenetic methods. 20,21 The extensive polymorphism in HLA class I genes is thought to increase the repertoire of immune responses which an individual can mount.…”
Section: Correspondence: Stephen J O'brien Phd Laboratory Of Genomimentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, an analysis of complete cDNA sequences of 14 HLA-C alleles revealed that HLA-C alleles divide into two groups, one comprising the Cw7 sero-type, and the other group including all remaining alleles. 19 These and other studies have sought to elucidate the sequence relationships of a subset of HLA class I alleles by parsimony or distance-based phylogenetic methods. 20,21 The extensive polymorphism in HLA class I genes is thought to increase the repertoire of immune responses which an individual can mount.…”
Section: Correspondence: Stephen J O'brien Phd Laboratory Of Genomimentioning
confidence: 99%
“…Sequence analysis suggests HLA-C is more closely related to HLA-B than HLA-A and indicates the HLA-C locus may have arisen as a duplication of HLA-B. 24 HLA-C homologues have been identified in the chimp 30,31 and gorilla 19 but are not found in genome or transcript searches of Asian apes (Old World primates, orangutans, gibbons or rhesus monkeys). The suspected recent origin of the HLA-C locus may explain the more conservative nature of the phylogenetic analyses presented here.…”
Section: Hla-cmentioning
confidence: 99%
“…In addition, both HLA-C variants are present in gorilla (Lawlor et al 1991) and bonobo (Cooper et al 1998). One might expect gibbons (the lesser apes) to be intermediate between Old World monkeys and the great apes, but a recent study (Abi-Rached et al 2010a) has shown that their MHC class I ligands to have pursued quite a different course of evolution.…”
Section: Hla-c Ligands and Kirs In Non-human Primatesmentioning
confidence: 99%
“…Rhesus macaques express orthologues of the classical HLA-A and -B genes, but not orthologues of HLA-C (8). Orthologues of HLA-C have been identified in chimpanzees, gorillas, and orangutans (2,24,25), but not in Old World monkeys (1). Hence, the HLA-C locus appears to represent a recent duplication of the HLA-B locus that occurred after the divergence of apes from Old World monkeys (1,8,15).…”
mentioning
confidence: 99%